A new Neotropical genus of bee flies (Diptera, Bombyliidae, Phthiriinae) - Yamaguchi, Carolina; Lamas, Carlos José E.; Evenhuis, Neal L. (Zootaxa, 2017)
A new genus of Phthiriinae, Hirsutophallus gen. nov. is described, based on the examination of male and female specimens from the Andean region of Bolivia and Argentina. Hirsutophallus gen. nov. contains several characters that distinguish it from other Phthiriinae genera, such as: prominent tip on the lateral margin of the scape; lower lobes on epiphallus; prominent lateral lobes on epiphallus, with dorsal macrosetae; penial guide of distiphallus with long and dense macrosetae on dorsal surface; gonocoxite with medial process large basally and acute apex in lateral view, with short apical and ventral spines and posterior process with ventral spines; gonostylus with row of spines on apical third of dorsal and ventral surface and furca with V-shaped sclerites, with very long and curved parallel arms. The new genus, endemic to the Neotropical Region, is described to accommodate Hirsutophallus andinus gen. nov. et sp. nov. An identification key to the genera of Phthiriinae is also provided. The species is described and illustrated in detail, including the male and female terminalia.